Applying Authentic Materials in Teaching English Grammar to Improve EFL Student’s Skills (Teachers’ Attitude) - Maher Ahmed Ali Saleh (Hasanuddin University, 2022)
The objective of this paper is basically to analyze the use of authentic materials in improving the understanding of students by teachers in teaching grammar in English as a foreign language (EFL) to the first-year students of Abyan University in South of Yemen. The teachers of EFL from faculties of education in Zingibar and Lowder participated in the current study. The paper is divided in two parts that is; the theoretical aspects and the practical aspects. Under the theoretical part the researcher describes the term grammar and authentic materials and gives reasons as to why teaching grammar using authentic materials can be beneficial in the learning process. The practical part on the other hand focuses on conducting interviews to the teachers. The results of the study revealed that most EFL teachers hold a positive attitude towards using authentic materials in teaching grammar. Therefore, positive reflections are observed from teachers who approve on Teaching and learning grammar proficiency with the use of authentic materials.